Reconstruction of the Early-Middle Miocene Palaeoenvironment in Gorongosa National Park, Mozambique - Maphutha, Mmatolo Julliet (University of the Witwatersrand, Johannesburg, 2025)
The origin of our flora and fauna is of general interest, and the Miocene (between 23.0 - 5.3 million years ago) was a crucial period for the development of our modern flora. Generally, there is a poor Miocene record in Africa but new Miocene sites have been discovered in Gorongosa National Park, central Mozambique; a park with an incredible diversity of fauna and flora. With newly discovered fossil shark teeth, molluscs, marine vertebrates and invertebrates, this is the first study to use palynological analysis to reconstruct the environment surrounding the Miocene fossils. The study aimed to use pollen, phytoliths, microcharcoal and other microremains to 1)reconstruct the palaeoenvironment and palaeoclimate from Early-Middle Miocene sediment deposits at the Gorongosa Palaeontological Locality number 12 (GPL-12); and 2)test the fidelity of the microremains recorded in the modern soils of the known vegetation types in the park. The pollen and phytolith samples for both fossil sediments and modern soils were processed using the standard method, which involves acid treatment and analysed in the lab. Overall, fungal material dominated most of the slides, and fossil non-pollen palynomorphs (NPPs) aided the most in palaeoenvironment reconstruction compared to fossil pollen and phytoliths. Fourteen phytolith morphotypes were found across the modern soil samples of which nine distinctively belonged to C4 grasses, the others were non-specific, and the rest were from woody dicotyledons. Overall, the results support other publications done in the area that the sea was more inland during the Miocene and GPL-12 was more wet and of an estuarine environment.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Palaeontology at the Evolutionary Studies Institute, to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2025
Keywords: Gorongosa National Park; Miocene; Palaeoenvironment; Palynology; Non-pollen palynomorphs; UCTD; SDG-15: Life on land; SDG-11: Sustainable cities and communities